Словарь антонимов русского языка: более 2 000 антонимических пар / М. Р. Львов ; редактор Л. А. Новиков - Львов Михаил Ростиславович (Русский язык, 1984)
Экземпляры: ф.4 (20170420) / Инвентарный номер: 016827 / Цена: 2.10 / Авт.знак: Л 89 / ГРНТИ: 16.21.47 / ББК: 81.2Рус-4